Implementasi Permainan Warna untuk Menstimulasi Keterampilan Observasi dan Eksperimen Sederhana pada Anak Usia Dini - Qurrotul Aini; Ardhana Reswari (JCE (Journal of Childhood Education), 2026)
Early childhood is a golden phase of cognitive development that requires appropriate stimulation to build science literacy from an early age, but the available science learning media are often too abstract and unsuitable for children's developmental characteristics. This study aims to describe the implementation of color games to stimulate observation and simple experimentation skills in early childhood. The study used a descriptive qualitative approach with 22 subjects aged 5-6 years in group B at Al-Falah Dempo Barat Pasean Pamekasan Kindergarten. Data were collected through participatory observation, in-depth interviews with two teachers, and documentation over eight weeks. The results showed that the implementation of color games was carried out in three stages, namely exploration of primary colors, simple color mixing using food coloring, clear plastic cups, water, spoons, and tissues, and advanced color experiments. The majority of children (19 out of 22 children) were able to identify color changes accurately, and most children (17 out of 22 children) successfully completed the simple experiment stages from prediction to verification of results. Children developed patterns of social interaction through collaboration, dialogue, and independent exploration. Supporting factors for implementation included concrete and interesting media, high enthusiasm among children, and an adequate teacher-to-child ratio, while inhibiting factors included technical challenges in using the media, variations in motor skills among children, and the need for intensive preparation. The study concluded that color games effectively stimulate observation and simple experimentation skills in early childhood, providing a theoretical contribution that reinforces Piaget's constructivism and Vygotsky's zone of proximal development, as well as a practical contribution in the form of an affordable and applicable alternative science learning medium for early childhood education teachers.